A “(re)descoberta do Mistério Pascal” no ideário neocatecumenal : paradigmas judaicos em uma iniciação cristã - Santos, Genisson Melo dos (2019)
The Second Vatican Council was responsible for various changes in the Roman Catholic Church. This is demonstrated in different ways, affecting primarily the liturgical and pastoral aspects. Our research aimed to analyze the way the itinerary called the Neocatechumenal Way works in this context of renewal, seeking, above all, to emphasize the way in which transformations in the liturgical and catechetical field work. Therefore, we got as a formal object the aesthetic and musical skills produced or adapted by the group and that take place in their celebrations. This movement that presents itself as an itinerary of Christian initiation of adults has a series of peculiar characteristics, especially concerning the contribution of elements originating from Judaism within its ideals. Our research focused on the analysis of how the use of elements of another religious tradition legitimizes institutionally in the scope of modernity, pointing to the tensions that arise from the modulation of the Catholic liturgy handled by this group of lay bias, which marks one of the various possibilities of the Catholic confessional heritage discovery that emerged after the Second Vatican Council. Finally, we point out the paradigmatic shifts proposed by the neocatechumenal ideology and how it presents itself as a proposal to rescue an integral experience of Christianity, where the encounter with the Sacred is indicated through the biographical participants paths, within their own concrete situations.